INNOVATION IN HOLISTIC HEALTH PROMOTION FOR SMOKERS: DEVELOPMENT OF A LEMONGRASS (Cymbopogon citratus) ESSENTIAL OIL HERBALINHALER - Titin Andri Wihastuti; Mayu Rahmayanti; Kumboyono Kumboyono (NurseLine Journal, 2025)
Background: Community nurses play a collaborative role in developing holistic complementary therapies for smoking cessation. Lemongrass (Cymbopogon citratus) essential oil, known for its anxiolytic properties, was formulated into a herbal inhaler as a candidate Nicotine Replacement Therapy (NRT) to complement psychological and behavioral interventions for smokers.Objective: This study aimed to evaluate smokers' acceptance of the lemongrass-based herbal inhaler as a potential NRT. Methods: Threeinhaler formulations were developed, with lemongrass essential oil as the active ingredient. Stability testing was tested among 90 participants over a 4-week storage period, assessing homogeneity and power of Hydrogen (pH) levels. Results: Results indicated no significant differences in homogeneity or pH across the storage period, with p-values at week 0, 1, 2, 3, and 4 being 0.716, 0.754, 0.771, 0.710, and 0.674, respectively (p> 0.05). Conclusion: The findings demonstrate that the lemongrass essential oil herbal inhaler exhibits favorable physical stability and is well-accepted by smokers as a smoking cessation therapy.